2020
DOI: 10.1016/j.mayocpiqo.2019.08.001
|View full text |Cite
|
Sign up to set email alerts
|

Relationships Among Organizational Values, Employee Engagement, and Patient Satisfaction in an Academic Medical Center

Abstract: Objective: To examine the relationships among various organizational values, employee engagement, and patient satisfaction in an academic medical center.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 23 publications
1
18
0
Order By: Relevance
“…Then the results of hypothesis testing can be concluded that employee engagement has a positive and significant effect on employee performance at the Regional General Hospital dr. Zainoel Abidin Banda Aceh. Employee engagement is an employee's enthusiasm for work that occurs because employees direct their energies to work in line with the company's strategic priorities (Afendi et al, 2020;Asih & Dewi, 2017;Kang et al, 2020;Pringgabayu & Kusumastuti, 2016). This spirit is formed because employees feel attached to the organization so that it has a positive potential for the organization, namely an increase in income.…”
Section: Discussionmentioning
confidence: 99%
“…Then the results of hypothesis testing can be concluded that employee engagement has a positive and significant effect on employee performance at the Regional General Hospital dr. Zainoel Abidin Banda Aceh. Employee engagement is an employee's enthusiasm for work that occurs because employees direct their energies to work in line with the company's strategic priorities (Afendi et al, 2020;Asih & Dewi, 2017;Kang et al, 2020;Pringgabayu & Kusumastuti, 2016). This spirit is formed because employees feel attached to the organization so that it has a positive potential for the organization, namely an increase in income.…”
Section: Discussionmentioning
confidence: 99%
“…The phenomenon of increasing competence, meeting motivational needs, and the limitations of the available learning environment are three components that significantly affect teacher performance and education quality (Kang et al, 2019). It can be seen that as a result of the three components still need to be improved; the teacher seeks to enhance the quality of teaching outcomes, punctuality in completing the curriculum and lesson plans is not late, is required to have the initiative in completing work, strives to have the ability to meet the teaching and learning process well, and improves the application of fostering cooperation between teachers and students (Van den Berghe et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…However, with an ever-increasing dependence on distractive technologies maintaining EE at workplace is becoming a next to impossible thing ( Farooq et al., 2017 ; Farooq and Salam, 2020 ; Jena et al., 2018 ; Kang et al., 2019 ; Ngo et al., 2020 ). Therefore, Rich et al.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Their results have established that EE is significantly influenced by the implementation of CSR in commercial airlines ( Farooq and Salam, 2020 ). However, still not much is known regarding the role and significance of EE in the garments manufacturing industry ( Farooq and Salam, 2020 ; Jena et al., 2018 ; Kang et al., 2019 ; Veleva et al., 2017 ). Therefore, it is predictable that the results derived from this comprehensive study can offer some new comprehensions regarding the role and significance of EE in the garments manufacturing industry.…”
Section: Literature Reviewmentioning
confidence: 99%